A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF BUSSINESS ENGLISH STUDY PROGRAM BENGKALIS STATE POLYTECHNIC IN SUMMARIZING ENGLISH TEXT - Boni Saputra (Politeknik Negeri Bengkalis, 2016)
Abstract: The ability of summarizing is essential to be acquired by students. In writing, students often summarize when quoting opinions and writing papers. This descriptive research is aimed at finding students’ level of ability in summarizing an English text as well as the highest and the lowest aspects of writing. Population of the research was second year students of Business English Study Program Bengkalis State Polytechnic consisting of 48 students. Technique of sampling used was random sampling technique. The chosen samples were 24 students of the population. Data and information were gathered by a writing test. The students were asked to write a good summary of a text given. The findings revealed that the ability level of students in summarizing text was in fairly good. While the second highest was in good category. This finding was based on the highest percentage of students’ score in summarizing of a text. In addition, the findings also explain that the highest aspect of writing was on fluency while the lowest percentage was on organization. It can be concluded that the students have good ability in summarizing English text. Keywords : Students’ Ability, Summarizing, Text